2016
DOI: 10.2527/jas.2015-9658
|View full text |Cite
|
Sign up to set email alerts
|

Sampling procedure for the measurement of dissolved hydrogen and volatile fatty acids in the rumen of dairy cows1

Abstract: Dissolved hydrogen (dH) influences the pathways of VFA production and is a precursor of methane formation in the rumen. Measurements of dH in rumen fluid taken at the same time as measuring other rumen fermentation end products would improve our quantitative understanding of the role of dH as a controller of rumen fermentation. Sample collections though a rumen cannula and using oral stomach tubing were compared for measurements of dissolved gases and fermentation end products in the rumen fluid of 4 ruminally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
51
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 28 publications
8
51
1
1
Order By: Relevance
“…Shen et al (2012) observed a tendency for total VFA concentration to be lower in ororuminal samples compared with rumen cannula samples. Previous stud-ies have observed problems with saliva contamination in ororuminal samples and attribute observed differences from ruminal cannula samples to this contamination (Duffield et al, 2004;Wang et al, 2016). The positive and negative correlations between extent of saliva contamination and pH or total VFA (Table 3), respectively, observed in the current study indicate that saliva contamination caused the higher pH and lower VFA concentrations in FLORA samples.…”
Section: Technical Notesupporting
confidence: 61%
See 2 more Smart Citations
“…Shen et al (2012) observed a tendency for total VFA concentration to be lower in ororuminal samples compared with rumen cannula samples. Previous stud-ies have observed problems with saliva contamination in ororuminal samples and attribute observed differences from ruminal cannula samples to this contamination (Duffield et al, 2004;Wang et al, 2016). The positive and negative correlations between extent of saliva contamination and pH or total VFA (Table 3), respectively, observed in the current study indicate that saliva contamination caused the higher pH and lower VFA concentrations in FLORA samples.…”
Section: Technical Notesupporting
confidence: 61%
“…However, the relative proportions of acetate, propionate, and butyrate were not affected by technique (P ≥ 0.44). Wang et al (2016) also observed pH to be higher, total VFA concentration to be lower, and VFA proportions not to differ in samples obtained via an ororuminal device compared with samples obtained through a rumen cannula. Shen et al (2012) observed a tendency for total VFA concentration to be lower in ororuminal samples compared with rumen cannula samples.…”
Section: Technical Notementioning
confidence: 66%
See 1 more Smart Citation
“…Differences observed in results from the present study may be related to the ruminal site of sampling as the rumen is not a completely homogeneous environment. The cranial ventral sac, which was the sampling site in this study, is known to have a higher total VFA concentration, lower pH, and differ in its microbiota and activity compared to the central rumen sacs (Martin et al, 1999; Wang et al, 2016a). Another possible explanation is that the increased concentration of planktonic bacteria with linseed oil was caused by a decreased number of bacteria able to colonize the feed particles (Duval et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ruminal fermentation products were affected by sampling time relative to feeding (Wang et al., ). Ruminal pH is one of the main fermentation variables directly affecting microbial growth, and consequently ruminal fermentation (Li, Penner, Hernandez‐Sanabria, Oba, & Guan, ).…”
Section: Discussionmentioning
confidence: 99%